2004
DOI: 10.1212/01.wnl.0000145761.38400.65
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a 6-month exercise program on patients with multiple sclerosis

Abstract: Walking speed improved in this randomized study. The results confirm that exercise is safe for multiple sclerosis patients and should be recommended for those with mild to moderate disability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
175
3
5

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 216 publications
(186 citation statements)
references
References 27 publications
3
175
3
5
Order By: Relevance
“…Wheras DeBolt and McCubbin (2004) showed that balance did not change after 10-weeks training. Romberg et al (2004), also did not reported any change for balance after 6 months exercise program (strength training and aquatic training) for MS patients with mild to moderate disability (EDSS 1.0 to 5.5).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Wheras DeBolt and McCubbin (2004) showed that balance did not change after 10-weeks training. Romberg et al (2004), also did not reported any change for balance after 6 months exercise program (strength training and aquatic training) for MS patients with mild to moderate disability (EDSS 1.0 to 5.5).…”
Section: Discussionmentioning
confidence: 82%
“…For example Mostert and Kesselring reported improvement in aerobic threshold, work rate and activity level after 4 weeks of aerobic exercise training (Mostert, 2002). Also treadmill training, aquatic, cycling and resistance training may be beneficial for patients with MS (White, 2004, Newman, 2007, Romberg, 2004, Rampello, 2007, Snook, 2009.…”
Section: Introductionmentioning
confidence: 99%
“…28 Blin ding of the ra pists and blin ding of pa ti ents we re the most com mon fa i lu re; no ne of the stu di es ac hi e ved the se two cri te ri a. Not using an in ten ti on-to-tre at analy sis was anot her most com mon met ho do lo gi cal fa i lu re; only one study 24 met this cri te ri on.…”
Section: Met Ho Do Lo Gi Cal Qu a Litymentioning
confidence: 90%
“…Eight stu di es we re consi de red as high-qu a lity (PED ro sco re ≥ 6). [20][21][22][23][24][25][26][27] Only one study was con si de red as low-qu a lity (PED ro sco re < 6). 28 Blin ding of the ra pists and blin ding of pa ti ents we re the most com mon fa i lu re; no ne of the stu di es ac hi e ved the se two cri te ri a.…”
Section: Met Ho Do Lo Gi Cal Qu a Litymentioning
confidence: 99%
See 1 more Smart Citation